Immunogenicity of COVID-19 Tozinameran Vaccination in Patients on Chronic Dialysis - Schrezenmeier, Eva; Bergfeld, Leon; Hillus, David; Lippert, Joerg-Detlev; Weber, Ulrike; Tober-Lau, Pinkus; Landgraf, Irmgard; Schwarz, Tatjana; Kappert, Kai; Stefanski, Ana-Luisa; Sattler, Arne; Kotsch, Katja; et al. (Frontiers in Immunology, 2021)
Patients with kidney failure have notoriously weak responses to common vaccines. Thus, immunogenicity of novel SARS-CoV-2 vaccines might be impaired in this group. To determine immunogenicity of SARS-CoV-2 vaccination in patients with chronic dialysis, we analyzed the humoral and T-cell response after two doses of mRNA vaccine Tozinameran (BNT162b2 BioNTech/Pfizer). This observational study included 43 patients on dialysis before vaccination with two doses of Tozinameran 21 days apart. Overall, 36 patients completed the observation period. Serum samples were analyzed by SARS-CoV-2 specific antibodies ~1 and ~3-4 weeks after the second vaccination. In addition, SARS-CoV-2-specific T-cell responses were assessed at the later time point by an interferon-gamma release assay (IGRA). Outcomes at later timepoints were compared to a group of 44 elderly patients with no dialysis after immunization with Tozinameran. Only 20/36 patients (55.6%, 95%CI: 38.29-71.67) developed SARS-CoV-2-IgG antibodies at first sampling, whereas 32/36 patients (88.9%, 95%CI:73.00-96.38) demonstrated seropositivity at the second sampling. Seroconversion rates and antibody titers were significantly lower compared to a cohort of vaccinees with similar age but no chronic dialysis (>90% seropositivity). SARS-CoV-2-specific T-cell responses 3 weeks after second vaccination were detected in 21/31 vaccinated dialysis patients (67.7%, 95%CI: 48.53-82.68) compared to 42/44 (93.3%, 95%CI: 76.49-98.84) in controls of similar age. Patients on dialysis demonstrate a delayed, but robust immune response three weeks after the second dose, which indicates effective vaccination of this vulnerable group. However, the lower immunogenicity of Tozinameran in these patients needs further attention to develop potential countermeasures such as an additional booster vaccination.